Serum Concentration of the Phytohormone Abscisic Acid Is Associated With Immune-Regulatory Mediators and Is a Potential Biomarker of Disease Severity in Chronic Obstructive Pulmonary Disease - Hoang, Quynh Trang Mi; Nguyen, Van Kinh; Oberacher, Herbert; Fuchs, Dietmar; Hernandez-Vargas, Esteban A.; Borucki, Katrin; Waldburg, Nadine; Wippermann, Jens; Schreiber, Jens; Bruder, Dunja; Veluswamy, Priya (Frontiers in Medicine, 2021)
COPD and asthma are two distinct but sometimes overlapping diseases exhibiting varying degree and types of inflammation on different stages of the disease. Though several biomarkers are defined to estimate the inflammatory endotype and stages in these diseases, there is still a need for new markers and potential therapeutic targets. We investigated the levels of a phytohormone, abscisic acid (ABA) and its receptor receptors, LANCL2 in COPD patients and asthmatics. In addition, PPAR-γ that is activated by ABA in a ligand binding domain independent manner, was also included in the study. LANCL2 and PPAR-γ in COPD patients and asthmatics and In this study, we correlated ABA with COPD propagating factors to define the possible role of ABA, in terms of immune-regulation, inflammation and disease stages. We collected blood from 101 COPD patients, 52 asthmatics and 57 controls. Bronchoscopy was performed on 5 COPD patients and 29 controls. We employed (i) liquid chromatography-tandem mass spectrometry and HPLC to determine the ABA and indoleamine 2, 3-dioxygenase levels, respectively; (ii) Real-time PCR to quantify gene expression of ABA receptors LANCL2 and PPAR-γ; (iii) Flow cytometry to quantify adipocytokines; (iv) Immunoturbidimetry and ELISA to measure CRP and cytokines, respectively. Finally, a multinomial regression model was used to predict the probability of using ABA as a biomarker. Blood ABA levels were significantly reduced in COPD patients and asthmatics compared to age- and gender-matched normal controls. The ABA receptor However, PPAR-γ was elevated in COPD patients. Intriguingly, ABA was positively correlated with immune-regulatory factors and was negatively correlated with inflammatory marker, in COPD. Of note, ABA was increased in advanced COPD stages. We thereby conclude that ABA might be involved in regulation of COPD pathogenesis and might be regarded as a potential biomarker for COPD stages.